2022
DOI: 10.3762/bjoc.18.184
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion complexes of the steroid hormones 17β-estradiol and progesterone with β- and γ-cyclodextrin hosts: syntheses, X-ray structures, thermal analyses and API solubility enhancements

Abstract: Overcoming the challenges of poor aqueous solubility of active pharmaceutical ingredients (APIs) is necessary to render them bioavailable. This study addresses the poor solubility of two potent steroid hormones, 17β-estradiol (BES) and progesterone (PRO), via their complexation with two water-soluble native cyclodextrins (CDs) namely β-CD and γ-CD. The hydrated inclusion complexes β-CD·BES, β-CD·PRO, γ-CD·BES and γ-CD·PRO were prepared via kneading and co-precipitation, and 1H NMR spectroscopic analysis of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…It has also been shown that the complexation of EST with this particular cyclodextrin decreased toxicity of the studied hormone [23]. Moreover, the combination of EST and ß-CD was found to improve the bioavailability of the API by increasing its solubility [28].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It has also been shown that the complexation of EST with this particular cyclodextrin decreased toxicity of the studied hormone [23]. Moreover, the combination of EST and ß-CD was found to improve the bioavailability of the API by increasing its solubility [28].…”
Section: Discussionmentioning
confidence: 92%
“…As was mentioned above, a single crystal analysis of the EST/ß-CD complex has been presented in a previous work [28] where only the host and the water oxygen atoms were located via the collected diffraction data using a Mo X-ray source, whereas the encapsulated hormone was not possible to be modeled as the residual electron density appearing within the host cavity was very low (∆ρ ≤ 1 e•Å 3 ) due to the high disorder of the included estradiol. Similar to that work, the EST/ß-CD crystal structure presented here was found to belong to the monoclinic system with space group C2, with roughly the same lattice parameters (Table 1).…”
Section: Scxrd Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Storing the complex for further use should be carried out at low temperature; for example, at 4 • C [98]. The current state of knowledge regarding the stoichiometry of the complexes indicates a 1:1 [98][99][100] value for HP-β-CD and β-CD or a 2:1 [99,100] for β-CD in the form of polymer-based materials. The 1:1 stoichiometry with β-CD was also shown to be stable in a molecular modeling study [101].…”
Section: Estradiol (E2) 421 Complex Preparation Methodsmentioning
confidence: 99%
“…Some diffraction lines of the pure steroid and for the oxymetholone-beta-cyclodextrin complex appear by random coincidence at similar 2ϴ, but still they are slightly shifted, which suggests that the inclusion of the steroid, which is a small molecule, is easily fitted inside the cyclodextrin cavity. Some preparations of beta-cyclodextrin with other steroidal compounds such as methyltestosterone [38], estradiol [39], and progesterone [40] have been recently reported.…”
Section: X-ray Powder Diffraction Analysismentioning
confidence: 99%